For an integrated management of household and similar waste in the city of Bejaia: Outline of a coordination approach between the actors - Aid, Abdelhalim; Bouadam, Roukia (Journal of Architecture and environment of child, 2021)
The reality of our cities is presented with a degraded image of the living environment and no longer fulfils their function in an acceptable manner. This is largely linked to the way it is managed, in particular the management of its waste. most cities have become confused by the repercussions of mismanagement of the services concerned. The issue of integrated management of household and similar waste (IMHSW) has experienced a remarkable deficit. In order to project this problem in a concrete way, we have brought together the reality of (IMHSW) in the city of Bejaia which is limited to a non-participatory and integrative linear management. It seems to us that the absence of this participatory management has led to an amplification of the gravity of the waste problem. The objective of this paper is to demonstrate the importance of coordination between the actors of the city of Bejaia in the integrated management of household and similar waste (IMHSW). The study recommends that integrated waste management cannot be achieved through unilateral management and does not depend only on the management of a municipal cleaning center, but must integrate all relevant sectors.